Propagating the Concept of Rahmatan Lil ‘Aalamin through Suffistic Da’wah in East Kalimantan - Noorthaibah, Noorthaibah; Maula, Ishmatul (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Dawah plays a vital role in developing and disseminating Islam as it opens opportunities for Islamic teachings to be accepted and adapted in new environments with people from different cultures. In this context, Sufi preaching is one of the successful manifestations in the propagation of Islam due to its flexible nature, which is its characteristic feature. Therefore, this research aims to examine and identify the role of preaching in developing Sufism in East Kalimantan, particularly in the current era of globalization. This study employs a descriptive qualitative research approach, with research locations spread across several areas in East Kalimantan, including Samarinda, Kutai Kartanegara, Balikpapan, Kutai Timur, Bontang, and Paser. The research results indicate that the current societal conditions closely related to technological advancements and information necessitate the presence of more relevant forms of preaching. In this context, da'is are obliged to use digital media to convey Sufi teachings. They are expected to be proficient in utilizing technology to continue delivering their preaching in line with the progress of the times.